Neuropathic pain and Kv7 voltage-gated potassium channels: The potential role of Kv7 activators in the treatment of neuropathic pain. (July 2019) - Abd-Elsayed, Alaa; Jackson, Markus; Gu, Steven L; Fiala, Kenneth; Gu, Jianguo
Neuropathic pain conditions severely and chronically affect the quality of life in a large human population, but the pain conditions are not adequately managed due to poor understanding of their underlying mechanisms. There is a pressing need for further research into this field to help develop effective and nonaddictive medications to treat neuropathic pain. This article first describes general clinical classification of pain, types and symptoms of neuropathic pain, and current practices of clinical management for neuropathic pain. This is followed by a discussion of various cellular and molecular mechanisms responsible for the development and maintenance of neuropathic pain. In this review, we highlight the loss of function of Kv7 voltage-gated potassium as a mechanism of neuropathic pain and the potential use of Kv7 channel activator as subsequent treatment.